1980
DOI: 10.1128/aac.18.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of clinically significant bacterial organisms in vitro by 2-acetylpyridine thiosemicarbazones

Abstract: Antibacterial activity of 65 2-acetylpyridine thiosemicarbazones and related compounds was determined by using clinical isolates of nine bacterial genera. Minimal inhibitory concentrations (MICs) of 0.002 to 0.062 ,ug/ml were obtained with 23% of the compounds for Neisseria gonorrhoeae and 0.016 to 0.062 ug/Iml with 17% of the compounds for N. meningitidis. Staphylococcus aureus was inhibited in the MIC range of 0.125 to 0.5 /Lg/ml by 18% of the thiosemicarbazones, whereas 26% inhibited group D enterococcus wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 7 publications
(6 reference statements)
2
46
0
Order By: Relevance
“…Here assay dependent artefacts were excluded by using two complementary viability assays ( Figure S2). In many cases not only free ligands, but also their metal complexes possess biological activity: picolinylidene TSC derivatives or their metal complexes have been reported to possess antimalarial [68], modest antibacterial [86], modest (to no) antifungal [87,88], but promising antitumor activity [88][89][90]. Salicylidene TSCs form redox-active complexes with various metal ions, including Ru(II) [91,92] and Cu(II) [93][94][95].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Here assay dependent artefacts were excluded by using two complementary viability assays ( Figure S2). In many cases not only free ligands, but also their metal complexes possess biological activity: picolinylidene TSC derivatives or their metal complexes have been reported to possess antimalarial [68], modest antibacterial [86], modest (to no) antifungal [87,88], but promising antitumor activity [88][89][90]. Salicylidene TSCs form redox-active complexes with various metal ions, including Ru(II) [91,92] and Cu(II) [93][94][95].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Screening of the compounds against other pathogenic organisms revealed that the compounds also possessed additional antiparasitic [3], antimicrobial [4,5], and antineoplastic [6] activity. We have since discovered that a number of these compounds are active against herpes simplex virus types 1 and 2 (HSV-1 and HSV-2) and that some of the derivatives inhibit the in vitro replication of the virus to a greater extent than they inhibit cellular DNA or protein synthesis [7], To date we have examined 111 derivatives and have found that certain compounds are active both in vitro and in a cutaneous herpes guinea pig model [8].…”
mentioning
confidence: 99%
“…Synthesis of oximes, and their complexes with different transition metals are reported in the literature [1][2][3][4][5][6][7][8][9] and found to be active as antibacterial ,antitubercular 8 , antilepral 10 , antiviral 11 , antimalarial 12 and active against certain kinds of tumours 13,14 . In this paper, a novel series of transition metal complexes with oxime were synthesized and they were screened for antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%